Rancang Bangun Portal Manajemen Magang Berbasis Web di PT Carano Integrasi Teknologi - Wahyudi, Wahyudi; Marta, Rizkayeni; Huda, Yasdinul; Samala, Agariadne Dwinggo (Lembaga Yasin AlSys, 2025)
The internship administration process in many institutions, including PT Carano Integrasi Teknologi Padang, is still conducted manually and relies on physical documents, making it susceptible to inefficiencies, data loss, and errors in participant placement. This study aims to design and develop a web-based internship management portal to digitalize the entire internship process, from registration to participant evaluation. The research employs a software engineering method using a case study approach, implemented with the PHP programming language and the CodeIgniter framework. The developed portal includes features such as account registration, internship application verification, task management, report uploads, participant performance assessment, and automatic certificate issuance. The system is also equipped with an AI-powered chatbot for real-time information services. Technical evaluation was conducted to assess performance in terms of access speed and efficiency. The results demonstrate that the system effectively addresses various administrative issues, improves time efficiency, reduces the risk of document loss, and ensures appropriate participant placement based on competency through centralized capacity monitoring. Performance testing using GTmetrix indicates that the portal meets and even exceeds Google’s Core Web Vitals standards, with a Largest Contentful Paint (LCP) of 1.1 seconds, Total Blocking Time (TBT) of 0 ms, and a Cumulative Layout Shift (CLS) of 0, reflecting high loading speed, optimal responsiveness, and stable user interface layout.